Individualist and collectivist consumer motivations in local organic food markets. (February 2018) - Schrank, Zachary; Running, Katrina
Community-Supported Agriculture programs have become a popular model for providing consumers with direct economic engagement with independent local organic farms. The degree to which Community-Supported Agriculture members are unified in their identity and consumer interests, however, is unclear. One possibility is that mostly individual interests including supposed nutritional benefits, superior taste, and avoidance of synthetic pesticides motivate Community-Supported Agriculture members. Another is that they are motivated more by environmental and economic concerns at the collective level. Our study engages this debate by analyzing emergent themes in consumers' motivational narratives using interview data with 58 members of a Community-Supported Agriculture program in a large southwestern city in the United States. We find that Community-Supported Agriculture members are largely unified in their consumer orientation and pursue individualist and collectivist goals equally. In other words, Community-Supported Agriculture members are neither primarily altruistic nor egoistic consumers, but they approach their consumption as a holistic act. Specifically, they emphasize environmental issues and a commitment to sustainability through local organic consumption as a pathway to individual health. This suggests that an internally homogeneous, yet multidimensional, framework constitutes the motivational structure of local organic food consumption. We argue this framework aligns with an emerging eco-habitus exhibited in environmentally conscious market fields that translate into both collective and individual benefits.